The use of a computerized database to monitor vaccine safety in Viet Nam - Mohammad Ali; Canh Gia Do; John D. Clemens; Jin-Kyung Park; Lorenz von Seidlein; Minh Tan Truong; Thiem Dinh Vu; Tho Huu Le; Trach Duc Dang (The World Health Organization, 2005)
Health information systems to monitor vaccine safety are used in industrialized countries to detect adverse medical events related to vaccinations or to prove the safety of vaccines. There are no such information systems in the developing world, but they are urgently needed. A large linked database for the monitoring of vaccine-related adverse events has been established in Khanh Hoa province, Viet Nam. Data collected during the first 2 years of surveillance, a period which included a mass measles vaccination campaign, were used to evaluate the system. For this purpose the discharge diagnoses of individuals admitted to polyclinics and hospitals were coded according to the International Classification of Diseases (ICD)-10 guidelines and linked in a dynamic population database with vaccination histories. A case-series analysis was applied to the cohort of children vaccinated during the mass measles vaccination campaign. The study recorded 107 022 immunizations in a catchment area with a population of 357 458 and confirmed vaccine coverage of 87% or higher for completed routine childhood vaccinations. The measles vaccination campaign immunized at least 86% of the targeted children aged 9 months to 10 years. No medical event was detected significantly more frequently during the 14 days after measles vaccination than before it. The experience in Viet Nam confirmed the safety of a measles vaccination campaign and shows that it is feasible to establish health information systems such as a large linked database which can provide reliable data in a developing country for a modest increase in use of resources.